Sunday

April 20, 2014

April 20, 2014

Posted by **chris** on Thursday, September 6, 2012 at 9:57pm.

- math -
**Reiny**, Thursday, September 6, 2012 at 10:00pmI will assume you are solving.

divided each term by 2

x^2 + 9x - 10 = 0

(x+10)(x-1) = 0

x = -10 or x = 1

**Related Questions**

math - when I have (2x^(3)-18x)-(2x^(3)) / (x^(2)-9) am I suppose to be left ...

Math - How can we factor trinomial: 36x^2+18x+0 Is thislike this: 18x(2x+1)

math! - determine two geometreic sequences whose first terms are 18x-9, 2x+8 and...

Math - 9x^2+16y^2-18x+64y-71=0 find the coordinates of the center, the foci, and...

algebra - Reduce answers to lowest terms. 1.) 2x/2x^2+5x-3 + 5/x^2-9 = 2.) x-3/...

math - sums and differences of a rational algebraic expression 3/a + 2/ab + 1/...

Algebra - 4x^4-18x^2=0. I have to find out what x equals by factoring. What I ...

Math - The expression (3x+4) (2x-6) is equavalent to? 3x(2x-6)+4(2x-6) multipy ...

math - 2x^3+7x^3-18x-63

math - 18x - 16 + 6( 2 - 2x) = 50